2019
DOI: 10.3390/cancers11050720
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mesenchymal Stromal Cells Regulate Cell Migration of Atypical Teratoid Rhabdoid Tumor through Exosome-Mediated miR155/SMARCA4 Pathway

Abstract: Atypical teratoid/rhabdoid tumor (ATRT) is a rare pediatric brain tumor with extremely high aggressiveness and poor prognosis. The tumor microenvironment is regulated by a complex interaction among distinct cell types, yet the crosstalk between tumor-associated mesenchymal stem cells (tMSCs) and naïve ATRT cells are unclear. In this study, we sought to identify the secretory factor(s) that is responsible for the tMSC-mediated regulation of ATRT migration. Comparing with ATRT cell alone, co-culture of tMSCs or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Furthermore, miR-155 directly targeted and inhibited a series of genes (e.g. FOXO3, SMARCA4 or Ubiquilin-1) to participate in the biological process of tumor development (37)(38)(39)(40). To the best of our knowledge, the present study was the first to indicate that TERF1 may be a direct target of miR-155, as confirmed by a dual luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, miR-155 directly targeted and inhibited a series of genes (e.g. FOXO3, SMARCA4 or Ubiquilin-1) to participate in the biological process of tumor development (37)(38)(39)(40). To the best of our knowledge, the present study was the first to indicate that TERF1 may be a direct target of miR-155, as confirmed by a dual luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 65%
“…91 Exosomes from tumor-associated MSCs contained high levels of miR-155, which, after being taken up by atypical teratoid/rhabdoid tumor cells, could cause tumor suppressor genes SMARCA4 (direct target genes of miR-155) inhibition, and enhanced atypical teratoid/ rhabdoid tumor migration ability. 92 In addition, glioma-associated human MSCs, a potential new matrix component in glioma, could drive the invasibility of glioma stem cells (GSCs) and have been identified as a new therapeutic target in glioma. 93 miR-1587 in glioma-associated human MSCs derived exosomes promoted proliferation and clonal formation in GSCs by down-regulating the tumor-suppressive nuclear receptor corepressor NCOR1 in GSCs.…”
Section: Exosome and Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Multiple different molecular structures have been identified in the liquids of pediatric brain tumor patients and raised the interest of the scientific field. These biomarkers include circulating tumor cells (CTCs) [ 18 , 19 ], circulating tumor DNA (ctDNA) [ 7 , 18 , 19 ], cell-free DNA (cfDNA) [ 6 , 18 , 19 , 20 , 21 ], circulating proteins [ 6 , 8 , 19 , 20 ], extracellular vesicles and exosomes [ 5 , 18 , 22 , 23 , 24 , 25 , 26 ], micro-RNAs (miRNAs) [ 5 , 19 , 27 , 28 , 29 , 30 , 31 , 32 ], long non-coding RNA (lncRNA) [ 33 ] and other genetic alterations [ 28 , 34 , 35 , 36 , 37 , 38 ]. Detection of these biomolecules may offer advantages compared to surgical interventions.…”
Section: Introductionmentioning
confidence: 99%